A study on the effects of workforce diversity towards employee performance in organizations / Ashiq Mohd Bahar - Mohd Bahar, Ashiq (Faculty of Business and Management, 2015)
As Malaysia entered the twenty first century, interest and concerns on the subject of workforce diversity heightened among others. Workforce Diversity has become an increasing trend in Malaysia, and it is widely accepted by most of the organizations in this particular country. Especially for the Professional, Scientific, and Technical Services Sector, as these activities demands a high degree of expertise and knowledge. Thus, this research was conducted to study the effects of workforce diversity towards the employee performance in organizations, which mainly focus on ‘Research and Development of Microelectronics and Software Products’ Industry in Selangor State, Malaysia. Gender Diversity, Age Diversity, and Ethnic Diversity are the Workforce Diversity Dimensions that were considered as the Independent Variable, while Employee Performance was considered as the Dependent Variable. Questionnaires were distributed through self-administered and electronic/mail approach, with the implementation of Non-Probability Convenience Sampling Technique to 150 employees. A total of 109 feedbacks were obtained from the 150 targeted samples. The data collected were then analyzed in Statistical Package for the Social Sciences (SPSS) Software to accumulate the findings. The results generated indicate that, there are significant relationships between all of the identified Workforce Diversity factors (Gender, Age, and Ethnic Diversity) towards the Employee Performance in an organization. Hence, the results suggests that, workforce diversity should be practice in the workplace to enhance employee performance, which eventually contributes to the competitive advantage of the organization and improving the economic growth of the country.